2020
DOI: 10.21203/rs.3.rs-26745/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of sleep and associated factors among people living with HIV/AIDS on follow up at Ethiopian Zewditu Memorial Hospital,2018

Abstract: Background: Sleep disturbance is a common complaint in people living with HIV/AIDS. Individuals with it are less likely to adhere to their treatment, have decreased quality of life, have decreased work productivity, and have increased risk of psychiatric disorders, cardiovascular morbidity, and disease progression. However, sleep condition remains under-recognized by clinicians and is not well studied in Ethiopia. Therefore it is necessary to produce scientific evidence to fill the clinical knowledge gap and r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…The prevalence of poor sleep quality in PLWHA was 55.1% [95% CI: 50.1, 60.2] in this study. This study's findings were consistent with those of previous studies conducted in Mexico (58.6%) [ 27 ], Nigeria at Lagos State University Teaching Hospital (59.31%) [ 28 ], and Ethiopia at Zewditu Memorial Hospital (55.6%) [ 23 ],Metu hospital (57.1%) [ 29 ] and Hawassa Hospital (57.6%) [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of poor sleep quality in PLWHA was 55.1% [95% CI: 50.1, 60.2] in this study. This study's findings were consistent with those of previous studies conducted in Mexico (58.6%) [ 27 ], Nigeria at Lagos State University Teaching Hospital (59.31%) [ 28 ], and Ethiopia at Zewditu Memorial Hospital (55.6%) [ 23 ],Metu hospital (57.1%) [ 29 ] and Hawassa Hospital (57.6%) [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…The sample size was calculated using the single population proportion calculation with a 95% confidence interval, a 5% margin of error, and the prevalence of poor sleeping quality among HIV/ADIS patients (p = 55.6%) from a study conducted at Zewditu Memorial Hospital in Addis Ababa, Ethiopia [ 23 ]. The required sample size was calculated as follows: n = (Z/2) 2p (1-p)/d2 (Kelsey, 1996), n= (1.96)2(0.556) (1–0.556)/(0.05)2 = 379; adding a 10% non-response rate, the required sample size was calculated as 417 study individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the time since HIV/AIDS diagnosis and the duration of ART use in PWH in Profile 3 were shorter than those of their counterparts, which could make them more vulnerable to sleep disorders. Moreover, previous studies suggested a potential correlation between sleep disorders and cognitive impairment in PWH 48 , 49 . However, according to the symptom network of Profile 3 in Fig.…”
Section: Discussionmentioning
confidence: 92%
“…It was the first hospital that commenced and initiated the subsidized fee-based scheme of ART service in Ethiopia in 2003. Currently, there are about 7,674 active adults and 2,558 children in its follow-up nest [ 28 ].…”
Section: Methodsmentioning
confidence: 99%